209. THE EFFECT OF ENHANCED RECOVERY AFTER MINIMALLY INVASIVE ESOPHAGECTOMY: A RANDOMIZED CONTROLLED TRIAL. (24th September 2022) - Shen, Yaxing; Wang, Hao; Fang, Yong; Yin, Jun; Tan, Lijie
Abstract: The purpose of this randomized controlled trial was to determine if enhanced recovery after surgery (ERAS) would improve outcomes in patients undergoing minimally invasive esophagectomy (MIE) for esophageal cancer. Patients with esophageal cancer undergoing MIE between March 2016 and August 2018 were enrolled. Patients were randomly divided into 2 groups: ERAS+ group that received a guideline-based ERAS protocol, and ERAS- group that received standard care. The primary endpoint was morbidity after MIE. The secondary endpoints were the length of hospital stay and time to ambulation after the surgery. The perioperative results were also collected and compared. A total of 60 patients in the ERAS+ group and 58 patients in the ERAS- group were included. Demographic and clinical features were similar between the groups. Postoperatively, the overall morbidity rate was lower in the ERAS+ group (33.3% vs. 51.7%; p = 0.04), as was the pulmonary complication rate (16.7% vs. 32.8%; p = 0.04). The ERAS+ group began ambulation at a mean of 2.8 days, as compared to 3.3 days for the ERAS- group (P = 0.001). The length of hospital stay was similar between the groups (9 days vs. 9 days; p = 0.70). Implementation of an ERAS protocol for patients undergoing MIE resulted in earlier ambulation and lower complications, without a further change in overall length of hospital stay.